Pharmacodynamics of huaier aqueous extract against papillary thyroid carcinoma in vivo and in vitro - Fa-Zhan Xu MS; Lu-Lu Zheng MS; Jia-Bo Qin MS; Yi-Xuan Li MS; Ke-Hao Chen MS; Ling-Hui Dai MS; Qiao-Ling Zhu MS; Jian-Feng Sang MD (Integrative Cancer Therapies)
Papillary thyroid carcinoma (PTC) is the main type of malignant tumor of the thyroid gland in adults. Huaier, a traditional Chinese medicinal agent, has demonstrated antitumor efficacy across diverse malignant neoplasms. However, the specific impact of huaier in PTC remains insufficiently elucidated. In this study, we explored the function of huaier in PTC. We treated a PTC cell line (TPC-1) with varying concentration gradients of huaier and we observed that huaier effectively inhibited the proliferation of TPC-1 cells with an IC50 of 2.538 mg/ml. Huaier also modulated the cell cycle of the TPC-1 cell line, and induced apoptosis in TPC-1. Huaier treatment inhibited migration and invasion of TPC-1 cells. Further studies showed that in TPC-1 cells, huaier treatment inhibited the expression of the MAPK and HSP27/STAT3/AKT signaling pathway. We subsequently demonstrated in a nude mouse model that huaier treatment inhibited the progression of PTC tumors. In summary, our data suggest that huaier can inhibit the proliferation, migration, and invasion of PTC cells in vitro and the progression of PTC tumors in vivo, and that this effect may be related to the MAPK and HSP27/STAT3/AKT signaling pathway; therefore, huaier extract is expected to be a new direction for the treatment of PTC.